RNA-dependent DNA polymerase of an endogenous type C virus of mice: purification and partial characterization. - Hizi, A (1980)
An RNA-dependent DNA polymerase was isolated from purified virions of endogenous oncornaviruses released by the MOPC-315 murine myeloma cell line. Upon sodium dodecyl sulfate-polyacrylamide gel electrophoresis, the purified enzyme was found to consist of two major polypeptides with molecular weights of about 28,000 and 26,500. The active enzyme had a molecular weight of approximately 56,000, as calculated from its sedimentation on glycerol density gradients, indicating that it is probably a dimer of the two subunit polypeptides. The isolated MOPC-315 virus polymerase exhibited all three activities known to be found in the DNA polymerase from oncornaviruses, namely, an RNA-dependent DNA polymerase, a DNA-dependent DNA polymerase, and an RNase H. The RNA-dependent polymerase activity showed a prounced preference for Mn2+ over Mg2+, whereas the DNA-dependent and RNase H reactions were catalyzed by these two cations to an almost equal extent. The purified polymerase was found to be immunologically related to the polymerase of Rauscher murine leukemia virus.